CONSTANT MURLEY SCORE ON PATIENTS POST SUPRASPINATUS RECONSTRUCTION WITH MEMBRANE AMNION COMPOSITE AND FAT TISSUE ALLOGENIC MESENCHYMAL STEM CELL AUGMENTATION - Heri Suroto; Bayu Antara Hadi; Goklas Ridwan Ricardo Gultom (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: Rotator cuff tears are the most common cases in nontrauma upper extremities in group patient more than 50 years old. Incidence on rotator cuff can’t show the real population. New Approaches healing rotator cuff syndrome is tendon regeneration like mesenchymal stem cell injection and growth factor or tissue engineering that has been developed.Methods: Retrospective comparation study of 15 postsupraspinatus reparation patients who has been treated for more than 4 months at the Dr. Soetomo general hospital. Patients is divided into group undergone supraspinatus reparation and patient supraspinatus reparation with augmented by membrane amnion composite and mesenchymal stem cell. Its’ functional results were evaluated using constant murley score.Results: Pain score average on supraspinatus reparation patients which augmented by membrane amnion and mesenchymal stem cell and those without augmentation is 15 and 13.7 (p=0.036). Daily activity score average on patients with and without augmentation are 20 and 17 (p=0.037). Flexion score average on patients with and without augmentation are 10 and 8.6 (p=0.114). External rotation score average on patients with and without augmentation are 9.6 and 7.2 (p=0.004). Internal rotation score average on patients with and without augmentation are 9.2 and 7.2 (p=0.012).Conclusion: The constant murley score pain score, ADL score, external rotation score, and internal rotation score in the group with the addition of amniotic membrane and mesenchymal stem cells were significantly better than the group with supraspinatus repair only, but not significantly on the flexion score and lateral elevation score components.